Effect of organic manure on growth and yield of dwarf late napiergrass on rocky marginal land (Asian Journal of Agriculture, 2025)
Abstract. Wadi A, Akhsan F, Basri. 2025. Effect of organic manure on growth and yield of dwarf late napiergrass on rocky marginal land. Asian J Agric 9: 727-738. The use of organic manure is a sustainable strategy to improve forage production on low-fertility soils. This study evaluated the effect of different manure application levels on the growth and yield of Dwarf Late napiergrass (DL Napiergrass) cultivated on marginal land under a cut-and-carry system. The field experiment was conducted over two years in Galung Village, Barru District, South Sulawesi, Indonesia, using a randomized block design with four manure treatments: control (0.00), low (1.38), medium (2.88), and high (4.67 g N m-² per application), replicated three times. Manure was applied five times annually, and growth parameters, dry matter yield, nutrient content, and soil characteristics were measured. Data were analyzed using ANOVA and Duncan's Multiple Range Test (DMRT), while regression analysis assessed the relationship between Leaf Area Index (LAI) and Crop Growth Rate (CGR). Results showed that manure application significantly (P
Keywords: Dwarf late napiergrass, manure-based fertilization, marginal land